Bilateral Accessory Head of First Lumbrical: Anatomical Insight and Surgical Implications during Carpal Tunnel Release - Verma, Anand; Kumar, Karan; Patnaik, Madhumita; Gaikwad, Manisha R.; Ravi, Praveen Kumar (Acta medica Lituanica, 2026)
Lumbrical muscles are essential for the coordination and precise movement of the hand; although anatomical variation in these muscles is rare, they can have significant clinical consequences, especially when they affect the carpal tunnel. Accessory heads of lumbrical are infrequent, typically unilateral, and often asymptomatic. However, when these variants pass through the carpal tunnel, they may decrease the tunnel’s volume, compress the median nerve, and contribute to the onset of Carpal Tunnel Syndrome (CTS). We present a rare case of a bilateral Accessory Head of the first Lumbrical Muscle (AHFL) discovered during a routine cadaveric dissection of a 65-year-old male. Recognizing such variations is crucial in clinical practice, as abnormal muscle tissue can complicate the diagnosis and surgical treatment of CTS. Preoperative imaging and thorough intraoperative examination can assist in identifying these variants, thus enhancing surgical planning and reducing complications.